Offset reduction technique for motion control of two wheeled wheelchair - Ahmad, Salmiah (s.n, 2012)
This research embarks on investigations for modelling and control of a two-wheeled wheelchair system as means of mobility for the disabled and the elderly people. The two-wheeled wheelchair is considered as a double-link inverted pendulum, and mathematical model of the system is obtained.